Pengelolaan Dana Desa untuk Pemberdayaan Masyarakat - Utomo, Ujang Wahyu (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Empowerment of village communities is a way for the welfare of village communities in various aspects, through good management of village funds, the opportunity to empower communities is very easy to do with the support of programs that are right on target and quality human resources. This study generally aims to determine the management of village funds for community empowerment. The research method used qualitative with a descriptive approach, the data collection technique was carried out with a research library, and there were two sources of data, namely primary and secondary. Data analysis used descriptive data analysis with three stages of data reduction, data display, and drawing conclusions. The results showed that, (1) the management of village fund allocation (ADD) which was sourced from central and regional government financial balance funds for the 2018 and 2019 fiscal years in Tri Mulya Jaya Village had been implemented but the results were not optimal. There is an imbalance in budget absorption, almost 35% of which is spent on village administration. (2) accountability for the realization of the APBDes has also been carried out transparently and accountably, and (3) residents appreciate the results of development and community empowerment that have been implemented by the village government.